The Legal Framework for Regulating the Digital Economy: Protecting Consumers and Promoting Innovation - Agus Satory; Rashid Rahman; Rina Farah (Yayasan Adra Karima Hubbi, 2026)
Background. The rapid expansion of the digital economy has transformed global market structures, creating new opportunities for innovation while raising significant concerns regarding consumer protection, data governance, and regulatory coherence. Existing legal frameworks often struggle to address the complexity of cross-border digital transactions and platform-based business models, resulting in gaps that affect both market efficiency and user trust. Purpose. This study aims to examine the effectiveness of legal frameworks in regulating the digital economy, with a particular focus on balancing consumer protection and innovation. Method. A qualitative doctrinal and comparative legal research design is employed, analyzing statutory instruments, policy documents, and regulatory practices across selected jurisdictions. Data are systematically evaluated using thematic analysis and comparative legal matrices to identify patterns, strengths, and limitations in regulatory approaches. Results.The findings reveal that jurisdictions with coherent, adaptive, and enforceable legal frameworks demonstrate higher levels of consumer trust and innovation performance. Evidence indicates that regulatory quality, rather than regulatory intensity, determines the success of digital governance. Conclusion.The study concludes that an integrated and flexible legal framework is essential for sustaining digital market growth while ensuring consumer protection.